Faktor-faktor yang memengaruhi perilaku bullying pada anak usia sekolah: A systematic literature review - Eni, Rosmi; Rinancy, Hariet; Siagian, Siti Hotna (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Bullying is violent behavior carried out by individuals or groups on an ongoing basis against someone who is considered weak or helpless, either physically or psychologically. At school age children are at an essential stage in life, where children have a very large desire to face new things and will be easily influenced by the environment. Purpose: To determine the factors that influence bullying behavior in school-age children. Method: Systematic literature review research sourced from database sources, namely Google Scholar, Pubmed, and Science Direct. The keywords used are bullying, factors, and school children. 149 literatures were obtained, then for the assessment of the quality of the literature using the PRISMA method and 9 literatures were selected that met the inclusion criteria. Results: Of the 9 literatures examined regarding the factors that cause bullying in school-age children, all literatures stated that the most dominant factors causing bullying are family factors, peer influence and school environment. 5 of the literatures stated that the most dominant bullying factors in children are unpleasant experiences and social media influence, while 3 literatures stated that the bullying factors are personality and high self-esteem and substance use. Conclusion: Factors that influence bullying behavior in school-age children are family factors, children's bad experiences (bad experiences in childhood), peer or school factors, social media, and exposure to addictive substances. Therefore, appropriate intervention is needed to address these causal factors, so that the prevalence of bullying behavior in school-age children can decrease. Keywords: Bullying; School-Age Children; Violence. Pendahuluan: Bullying adalah perilaku kekerasan yang dilakukan oleh individu atau kelompok secara terus-menerus terhadap seseorang yang dianggap lemah atau tidak berdaya dapat dilakukan secara fisik maupun psikologis. Pada usia sekolah anak berada pada tahapan esensial dalam kehidupan, dimana anak memiliki angan yang sangat besar untuk menghadapi hal baru dan akan mudah terpengaruh oleh lingkungan. Tujuan: Untuk mengetahui faktor-faktor yang memengaruhi perilaku bullying pada anak usia sekolah. Metode: Penelitian systematic literature review berasal dari sumber database yaitu Google Scholar, Pubmed, dan Sciencedirect. Kata kunci yang digunakan adalah bullying, factor, dan anak sekolah. Didapatkan 149 literatur, kemudian untuk penilaian kualitas literatur menggunakan metode PRISMA dan terpilih 9 literatur yang sesuai dengan kriteria inklusi. Hasil: Dari 9 literatur yang diteliti, semua literatur menyatakan bahwa faktor yang paling dominan yang menyebabkan terjadinya bullying adalah faktor keluarga, pengaruh teman sebaya, dan lingkungan sekolah. 5 diantara literatur menyatakan, faktor bullying yang paling dominan pada anak adalah pengalaman yang tidak menyenangkan dan pengaruh media social. Sementara 3 literatur menyatakan, faktor bullying adalah kepribadian dan harga diri yang tinggi serta penggunaan zat adiktif. Simpulan: Faktor yang memengaruhi perilaku bullying pada anak usia sekolah adalah faktor keluarga, adverse children experience (pengalaman buruk di masa kecil), peer group atau faktor sekolah, media social, dan paparan zat adiktif. Oleh karena itu, perlunya intervensi yang tepat untuk mengatasi faktor penyebab tersebut, agar prevalensi perilaku bullying pada anak usia sekolah dapat menurun. Kata Kunci: Anak Usia Sekolah; Bullying; Kekerasan.